German emigration via Bremen in the Weimar Republic (1920-1932) - Christian Lumpe; Claudia Lumpe (Philipps-University Marburg, School of Business and Economics, 2017)
This paper analyzes the oversea emigration of German passengers via the port of Bremen in the period of theWeimar Republic (1920-1932). We use a novel micro-dataset of digitalized passengers lists including about 181,000 emigrants as an estimation of the outflow of Germans from the German Reich. The descriptive analysis shows that the dataset is overall representative compared to official statistics except for the years 1924 and 1929 in which the data loss is huge. Furthermore, we deduce the skill level of the emigrating working population on the basis of information about occupations in the dataset. We find that male migrants had higher skills than female migrants and that South American countries attracted a relatively better skill distribution than the United States although the latter represented the main destination country for emigrants of any skill level in absolute numbers.
Keywords: F22; N33; N34; O15; 330; Bremen; migration accounting; migratory outflows; skill level